Identification of the 10 Most Common Diseases in Primary Care Facilities for the Period January 2024 - December 2024 at the Faculty of Medicine Educational Facilities - Shafa Camilia Umar; Marliyanti Nur Rahmah Akib; Asrini Safitri; Suliati P. Amir; Sulmiawati, Sulmiawati (Jurnal EduHealth, 2025)
Health services are basically aimed at carrying out prevention and treatment efforts for a disease, including medical services based on the basis of individual relationships between doctors and patients who need healing for their illnesses. This study was conducted with the aim of knowing the 10 most common diseases in primary care facilities for the period January 2024 - December 2024 at the UMI medical faculty educational facility. Furthermore, this study uses a qualitative research type with a descriptive research design, using secondary data obtained from medical records, the sampling technique used in this study is the total sampling technique. And the data analysis technique uses univariate analysis techniques carried out by induction, namely by drawing general conclusions based on research that has been done at the beginning. The results of the study stated that the 10 most common diseases were obtained in all health centers that are educational facilities for the UMI medical faculty. With cases of non-communicable diseases. Non-communicable diseases include hypertension (25.91%), non-insulin DM (11.21%), diabetes mellitus (9.3%), gastritis (4.46%), myalgia (3.28%), and dermatitis (3.13%). Meanwhile, the infectious diseases listed are common cold (14.05%), acute rhinitis (13.82%), ARI (9.06%), and cough (5.76%).